ANALISIS FAKTOR – FAKTOR MOTIVASI DAN LATAR BELAKANG KELUARGA YANG BERPENGARUH TERHADAP NIAT KEWIRAUSAHAAN (Studi pada mahasiswa S1 Manajemen Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Anugrahi, Ausabelina; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the students motivation and the motivation factor to influence on entrepreneurial intention. The data of this research were collected through a questionnaire distributed to 77 students of the Faculty of Economics and Business. Mechanical testing of the data used in this research include the instrument test (validity, and reliability test, classical assumption test, multiple linear regression analysist, t test, F test, and coefficient of determination test using SPSS application. The result of this research shows that self efficacy and background of parents influence positively and significantly to the entrepreneurial intention. Meanwhile risk tolerance influence positively but not significantly to the entrepreneurial intention. Value of determination coefficient is 0,340 which means entrepreneurial intention is affected by risk tolerance, self efficacy and background of parents amounted to 34 %